Complex-phase gypsum base building material as well as preparation method and application thereof

By adding modifiers to the semi-water gypsum and dispersing them, compound gypsum is prepared, which solves the problems of semi-water gypsum agglomeration and unstable gelling activity, and achieves low-cost and efficient gypsum resource utilization , suitable for a variety of filling applications.

CN119118550APending Publication Date: 2024-12-13GUIZHOU CHANHEN CHEM CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411233778.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-04
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

When using semi-water gypsum in the prior art, there are problems such as high agglomeration strength, difficulty in transportation, high cost, high energy consumption and unstable gelling activity, making it difficult to achieve large-scale resource utilization.

Method used

By stirring and mixing the semi-water gypsum with a modifier, dispersing it after storage and conversion, a high-stable intermediate complex phase gypsum between the semi-water phase and the dihydrate phase is prepared, which delays the crystallization water conversion rate and reduces agglomeration The gelling activity is maintained without adding activity inhibitors or drying treatment, and the road mixing method is used to crush, replenish and compact mold.

Benefits of technology

It has achieved the reduction of the cost of resource utilization of gypsum, increased transportation radius, simplified operations, and improved the strength and integrity of compound gypsum. It is suitable for industrial site foundation filling, ecological restoration and roadbed filling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005027106060000091
    Figure BDA0005027106060000091
  • Figure BDA0005027106060000092
    Figure BDA0005027106060000092
  • Figure BDA0005027106060000093
    Figure BDA0005027106060000093
Patent Text Reader

Abstract

The invention belongs to the technical field of industrial byproduct ardealite recycling, and particularly relates to a complex-phase gypsum base building material as well as a preparation method and application thereof. The preparation method comprises the following steps: S1) stirring and mixing semi-hydrated gypsum and a modifier to obtain modified semi-hydrated gypsum; the initial free water content of the semi-hydrated gypsum is less than or equal to 18.0%, and the crystal water content is less than or equal to 9.0%; s2) carrying out stockpiling conversion on the modified semi-hydrated gypsum, and then scattering to obtain complex-phase gypsum; and S3) crushing the complex-phase gypsum, supplementing water, mixing, compacting and forming to obtain the complex-phase gypsum base building material. The high-stability intermediate complex-phase gypsum between a semi-aqueous phase and a two-aqueous phase is prepared under the condition that an activity inhibitor is not added or drying treatment is carried out, the conversion rate of crystal water is slowed down under the conditions of low free water, high void and high heat release, the caking strength of a pile body is low, and certain gelling activity can be kept; the resource utilization cost of the gypsum is greatly reduced, the operation is simple, and the transportation radius is increased.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of recycling industrial by-product phosphogypsum, and in particular relates to a complex phase gypsum base material, a preparation method and application thereof. Background Art

[0002] At present, the main by-product of the wet-process phosphoric acid production process of my country's phosphorus chemical enterprises is dihydrate gypsum (CaSO 4 ·2H 2 O) and hemihydrate gypsum (CaSO 4 1 / 2H 2 O). Dihydrate gypsum itself does not have gelling activity and is difficult to use directly. It usually needs to be dehydrated at high temperature to form semi-hydrated gypsum or added to cement and other gelling materials before use, but the cost is high in the process of large-scale utilization. In addition to high-temperature dehydration to form semi-hydrated gypsum, a small number of domestic companies currently use semi-hydrated wet phosphoric acid production technology. The by-product semi-hydrated gypsum itself has gelling activity, but semi-hydrated gypsum is an unstable phase and will quickly convert into dihydrate gypsum in a short period of time, lose its gelling activity, and form a block in the slag field, making it difficult to transport. The energy consumption and cost of post-agglomeration treatment are high, and the original gypsum contains impurities such as water-soluble phosphates, fluorides, and organic matter, which often require pretreatment to remove impurities. Therefore, it is difficult to achieve large-scale utilization.

[0003] Patent application document CN2021115339047 discloses a method and process for retarding the setting of gypsum, stabilizing hemihydrate gypsum, and inhibiting the transformation of hemihydrate gypsum. The technology uses a calcium alkaline agent and an inhibitor to work together to stabilize the hemihydrate gypsum. However, the disadvantage of this technology is that the active inhibitor is expensive. The active inhibitor is an alkali-active inhibitor. Only when the calcium alkaline agent is added in excess can it play an active inhibitory role. When it is applied in large quantities in the fields of industrial plant foundation filling, ecological restoration, roadbed filling, etc., the cost is huge.

[0004] In summary, under alkaline stimulation, when hemihydrate gypsum contains excessive free water, the crystal water will quickly transform into agglomerates, making long-distance transportation difficult, and it is impossible to unload the vehicle. The transportation radius is small and it is difficult to utilize. The traditional treatment method is mainly based on slag dump storage. After the hemihydrate gypsum ages to form dihydrate gypsum, it can only be used as an inert filler for secondary mining. In addition, during secondary mining, the dihydrate gypsum blocks have high strength, low mining efficiency, and greatly increased costs. In addition to the traditional method of stacking and preparing inert fillers for the use of hemihydrate gypsum, if the gelling activity of hemihydrate gypsum is to be fully utilized, it is necessary to add activity inhibitors or dry the free water at high temperature. The corresponding results are high cost, high energy consumption, and complex processes for the large-scale utilization of gypsum, making it difficult to use on a large scale. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide a complex gypsum base material, a preparation method and application thereof. The present invention prepares a highly stable intermediate complex gypsum between a semi-aqueous phase and a dihydrate phase without adding an activity inhibitor or drying treatment, so that the crystallization water conversion rate of the semi-hydrated gypsum is slowed down, the agglomeration strength is low, and a certain gelling activity can be maintained, which greatly reduces the cost of gypsum resource utilization, is simple to operate, and increases the transportation radius.

[0006] The present invention provides a method for preparing a multiphase gypsum base material, comprising the following steps:

[0007] S1) stirring and mixing hemihydrate gypsum and a modifier to obtain modified hemihydrate gypsum; the initial free water content of the hemihydrate gypsum is ≤18.0%, and the crystal water content is ≤9.0%;

[0008] S2) the modified hemihydrate gypsum is stored and converted and then dispersed to obtain xCaSO 4 0.5H 2 O·(1-x)CaSO 4 ·2H 2 O-type multiphase gypsum; wherein x=0.33-0.67;

[0009] S3) crushing the complex phase gypsum, adding water, mixing, compacting and forming to obtain a complex phase gypsum foundation material.

[0010] Preferably, in step S1), the chemical components of the hemihydrate gypsum include:

[0011] SO 3 40 wt%~55wt%, CaO 30wt%~35wt%, SiO 2 2 wt%~5wt%,Al 2 O 3 0.1wt%~2wt%,Fe 2 O 3 0 wt%~0.5wt%, MgO 0wt%~0.2wt%, total P 2 O 5 0.5 wt%~1.5wt%, water-soluble P 2 O 5 0.01 wt%~0.7wt%, total F 0.2wt%~1.5wt%, water-soluble F 0.02wt%~0.5wt%, K 2 O 0.01 wt%~0.2 wt%, Na 2 O 0.1wt%~0.5wt%.

[0012] Preferably, in step S1), the modifier includes calcium oxide, magnesium carbonate, cement, carbide slag, water treatment slag, mineral powder, biomass ash powder and CaCO 3 At least one of micro powders.

[0013] Preferably, in step S1), the mass ratio of the modifier to the hemihydrate gypsum dry matrix is ​​2-10:90-98.

[0014] Preferably, in step S2), the storage conversion time is 10h to 15d; the particle strength of the pile is ≤0.5MPa;

[0015] In the stockpile after the stockpile conversion, the free water content is ≤14%, and the crystal water content is 12% to 16%.

[0016] Preferably, in step S2), the blocks or particles are broken up into low-strength blocks or particles with a particle size of ≤0.5 MPa; among the low-strength blocks or particles, the mass proportion of blocks or particles with a particle size of ≥4.75 mm is more than 80%, and the maximum particle size does not exceed 25 cm; the breaking up is carried out using an excavator and / or a forklift.

[0017] Preferably, in step S3), the crushing device is a road mixer, and uses a deepened bullet-shaped stirring tooth, the stirring depth is ≥50 cm, and the particle size of the composite gypsum after crushing is ≤2 mm, accounting for more than 90%.

[0018] Preferably, in step S3), the free water content of the mixture after water replenishment and mixing is 18% to 20%, and the crystal water content is 12% to 16%;

[0019] The compaction degree of the compacted body after compaction molding is ≥90%.

[0020] The present invention also provides a multiphase gypsum foundation material prepared by the preparation method described above.

[0021] The present invention also provides an application of the above-mentioned multiphase gypsum foundation material in the fields of industrial site foundation filling, ecological restoration and roadbed filling.

[0022] The present invention provides a method for preparing a multiphase gypsum foundation material, comprising the following steps: S1) mixing hemihydrate gypsum with a modifier to obtain modified hemihydrate gypsum; the initial free water content of the hemihydrate gypsum is ≤18.0%, and the crystal water content is ≤9.0%; S2) the modified hemihydrate gypsum is piled up and transformed and then dispersed to obtain xCaSO 4 0.5H 2 O·(1-x)CaSO 4 ·2H 2O (x = 0.33 ~ 0.67) type multiphase gypsum; S3) the multiphase gypsum is crushed, watered and mixed, compacted and formed to obtain a multiphase gypsum foundation material. The present invention prepares a highly stable intermediate multiphase gypsum between a semi-aqueous phase and a di-aqueous phase without adding an activity inhibitor or drying treatment. Under low free water, high voids and high heat release, the crystallization water conversion rate of the semi-hydrated gypsum is slowed down, the agglomeration strength is low, and a certain gelling activity can be maintained, which greatly reduces the cost of gypsum resource utilization, is simple to operate, and increases the transportation radius.

[0023] The present invention adopts the road-mixing method for construction, which saves the cost of centralized factory mixing and dispersing. After the complex phase gypsum is crushed by road mixing, mixed with water, and rolled into shape, it has high strength, good integrity, and low permeability coefficient, and can be widely used in the fields of industrial site foundation filling, ecological restoration, roadbed filling, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The XRD diagram is a transformation from a hemihydrate gypsum with a crystal water content of 8.02% (mass content) to a complex phase gypsum with a crystal water content of 14.21% and then to a dihydrate gypsum with a crystal water content of 17.10%;

[0025] Figure 2 The SEM images of hemihydrate gypsum at different magnifications;

[0026] Figure 3 The SEM images of the multiphase gypsum at different magnifications;

[0027] Figure 4 This is a SEM image of a high-strength filling body formed by multiphase gypsum (with a crystal water content of 14.21%) after crushing, water replenishment, mixing, compaction and hydration;

[0028] Figure 5 This is a SEM image of a high-strength filling body formed by crushing, hydrating, mixing, compacting and hydrating hemihydrate gypsum (mass content of crystal water is 8.02%). DETAILED DESCRIPTION

[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] The present invention provides a method for preparing a multiphase gypsum foundation material, comprising the following steps:

[0031] S1) stirring and mixing hemihydrate gypsum and a modifier to obtain modified hemihydrate gypsum; the initial free water content of the hemihydrate gypsum is ≤18.0%, and the crystal water content is ≤9.0%;

[0032] S2) the modified hemihydrate gypsum is stored and converted and then dispersed to obtain xCaSO 4 0.5H 2 O·(1-x)CaSO 4 ·2H 2 O (x = 0.33 ~ 0.67) type multiphase gypsum;

[0033] S3) crushing the complex phase gypsum, adding water, mixing, compacting and forming to obtain a complex phase gypsum foundation material.

[0034] In step S1):

[0035] The semi-hydrated gypsum and the modifier are stirred and mixed to obtain modified semi-hydrated gypsum; the initial free water content (mass content) of the semi-hydrated gypsum is ≤18.0%, and the crystal water content (mass content) is ≤9.0%. The initial temperature of the semi-hydrated gypsum is 50-60°C, for example, 56°C.

[0036] In certain embodiments of the present invention, the chemical components of the hemihydrate gypsum include:

[0037] SO 3 40 wt%~55wt%, CaO 30wt%~35wt%, SiO 2 2 wt%~5wt%,Al 2 O 3 0.1wt%~2wt%,Fe 2 O 3 0 wt%~0.5wt%, MgO 0wt%~0.2wt%, total P 2 O 5 0.5 wt%~1.5wt%, water-soluble P 2 O 5 0.01 wt%~0.7wt%, total F 0.2wt%~1.5wt%, water-soluble F 0.02wt%~0.5wt%, K 2 O 0.01 wt%~0.2 wt%, Na 2 O 0.1wt%~0.5wt%.

[0038] In certain embodiments of the present invention, the modifier is selected from calcium oxide, magnesium carbonate, cement, carbide slag, water treatment slag, mineral powder, biomass ash powder and CaCO 3At least one of the fine powders. Mineral powder is the fine powder produced in mining, which is the powder and dust produced in the process of mining limestone ore, collected and screened, and is referred to as mineral powder.

[0039] In certain embodiments of the present invention, the mass ratio of the modifier to the hemihydrate gypsum dry matrix is ​​2-10:90-98, such as 7:93, 5:95.

[0040] The stirring and mixing is carried out in a double-shaft mixer.

[0041] In step S2):

[0042] The modified hemihydrate gypsum is piled up and transformed and then dispersed to obtain xCaSO 4 0.5H 2 O·(1-x)CaSO 4 ·2H 2 O (x = 0.33 ~ 0.67) type complex phase gypsum.

[0043] During the stacking conversion process, the material obtained in step S1) absorbs 0.5 to 1.0 free water molecules and is converted into xCaSO 4 0.5H 2 O·(1-x)CaSO 4 ·2H 2 O (x = 0.33 ~ 0.67) type complex phase gypsum.

[0044] In some embodiments of the present invention, the storage conversion time is 10h to 15d, such as 2d, 8d, 15d. The particle strength of the pile is ≤0.5MPa, such as 0.21MPa, 0.23MPa; the internal temperature of the pile is ≤60℃, such as 55℃, 57℃, 59℃.

[0045] In the stockpile after the stockpile conversion, the free water content (mass content) is ≤14%, such as 12.55%, 11.45%, 12.75%; the crystal water content (mass content) is 12% to 16%, such as 12.17%, 13.17%, 12.57%.

[0046] The pile can be broken up by excavators or forklifts. After breaking up, the internal temperature of the pile is released to 25-29°C, such as 27°C, 25°C, and 23°C.

[0047] The multiphase gypsum is a low-strength block or particle with a particle size of ≤0.5 MPa. Among the low-strength blocks or particles, the mass proportion of blocks or particles with a particle size of ≥4.75 mm is more than 80%, and the maximum particle size does not exceed 25 cm. The disintegration is carried out by an excavator and / or a forklift.

[0048] In certain embodiments, the mass percentage of lumps or particles with a particle size of ≥4.75 mm is 90%, 93%, and the maximum particle size is 23 cm, 24 cm.

[0049] In step S3):

[0050] The complex phase gypsum is crushed, watered and mixed, compacted and formed to obtain the complex phase gypsum foundation material.

[0051] In certain embodiments of the present invention, before the multiphase gypsum is crushed, the method further comprises:

[0052] The complex phase gypsum is transported to a filling site and spread loosely with a thickness of 45 to 55 cm, such as 50 cm.

[0053] In certain embodiments of the present invention, the crushing device adopts a road mixer, and uses a deepened bullet-shaped stirring tooth, the stirring depth is ≥50cm, and the particle size of the composite gypsum after crushing is ≤2mm accounts for more than 90%, such as 97%.

[0054] The water replenishment mixing adopts neutral water or alkaline water. The alkaline water is selected from water treatment slag slurry, ash emulsion slurry or other alkaline water; the mass concentration of water treatment slag slurry can be 15% to 25%. When neutral water is used, the water replenishment amount is 4% to 8%, such as 6%; the water replenishment adopts a mobile or fixed spray gun, and after the water replenishment, a road mixer is used to mix 1 to 2 times. When alkaline water such as water treatment slag slurry is used, the dry mass ratio of water treatment slag to complex phase gypsum is 1 to 2: 98 to 99. The free water content (mass content) of the obtained mixture is 18% to 20%, such as 18.55%, 18.33%, 18.23%; the crystallization water content (mass content) is 12% to 16%, such as 13.57%, 14.23%, 13.67%.

[0055] The compaction degree of the compacted body after compaction molding is ≥90%, such as 92.11% or 92.34%; the crystal water content (mass content) of the compacted body is 12% to 16%.

[0056] After the compaction molding, it also includes: hydration to obtain a multiphase gypsum foundation material. The hydration can be natural curing; the time is 6 to 8 days, such as 7 days. The crystalline water content (mass content) in the fully hydrated multiphase gypsum foundation material is 19% to 21%, such as 20%, 19.98%, 20.12%, 20.16%. The strength of the hydrated filling body (i.e., the multiphase gypsum foundation material) for 7 days (corresponding to the R7d strength in the following text) is ≥1.5MPa.

[0057] The present invention also provides a multiphase gypsum foundation material prepared by the preparation method described above.

[0058] The present invention also provides an application of the above-mentioned multiphase gypsum foundation material in the fields of industrial site foundation filling, ecological restoration and roadbed filling.

[0059] In the present invention, the chemical reaction principle for obtaining the complex phase gypsum is:

[0060] (1) Principle of preparing complex phase gypsum from hemihydrate gypsum (first stage reaction, corresponding to steps S1) and S2):

[0061] CaSO 4 0.5H 2 O+(0.5~1.0)H 2 O→(0.33~0.67)(CaSO 4 0.5H 2 O)·(0.33~0.67)(Ca

[0062] SO 4 ·2H 2 O);

[0063] Hemihydrate gypsum CaSO 4 0.5H 2 After absorbing 0.5 to 1.0 free water molecules, O gradually dissolves and crystallizes CaSO 4 ·2H 2 O, with incompletely dissolved 0.5H 2 O·CaSO 4 Formation of xCaSO 4 0.5H 2 O·(1-x)CaSO 4 ·2H 2 O (x = 0.33 ~ 0.67) type multiphase gypsum, at this time the crystal water content (mass content) is 12% ~ 16%. Figure 1 shown. Figure 1 The XRD diagram of the transformation of hemihydrate gypsum with a crystal water content of 8.02% (mass content) to complex phase gypsum with a crystal water content of 14.21% and then to dihydrate gypsum with a crystal water content of 17.10% shows that with the transformation of hemihydrate gypsum, the crystal water content increases, that is, at the same diffraction angle, the CaSO 4 0.5H 2 O characteristic diffraction peak intensity gradually weakens, CaSO 4 ·2H 2 O characteristic diffraction peak intensity gradually becomes stronger. Since the dihydrate gypsum phase in the complex phase gypsum has no gelling activity, its phase component content should not exceed 67%; while the incompletely dissolved square columnar hemihydrate gypsum phase is the main body of strength generation, and its phase component content should not be less than 33%, that is, xCaSO 4 0.5H 2O·(1-x)CaSO 4 ·2H 2 O (x = 0.33 ~ 0.67) type multiphase gypsum. Figure 1 It can be seen that the mineral phase component of the complex gypsum of the present invention is different from that of hemihydrate gypsum and dihydrate gypsum, and is between the two.

[0064] During the transformation of hemihydrate gypsum to complex phase gypsum, as the free water content in the gypsum gradually decreases, the transformation can be delayed to maintain a certain activity. At the same time, during the transformation of hemihydrate gypsum to complex phase gypsum, it obtains a slight strength, can maintain a block or granular state during the turning process, increases the porosity of the pile, releases the heat inside the pile, can further delay the transformation, and avoid secondary agglomeration after breaking up.

[0065] Figure 2 The SEM images of hemihydrate gypsum at different magnifications are shown below. Figure 2 Figure a is a SEM image of hemihydrate gypsum at a magnification of Mag = 1.00kx; Figure 2 Figure b is a SEM image of hemihydrate gypsum at a magnification of Mag = 500x.

[0066] Figure 3 The SEM images of the multiphase gypsum at different magnifications are shown in Figure 2. Figure 3 Figure a is a SEM image of the multiphase gypsum at a magnification of Mag = 5.00kx; Figure 3 Figure b is a SEM image of the complex phase gypsum at a magnification of Mag = 2.00kx.

[0067] from Figure 2 and Figure 3 It can be seen that the crystal morphology of the raw material hemihydrate gypsum and the prepared complex phase gypsum was observed under a SEM scanning electron microscope. The crystal morphology of the hemihydrate gypsum is mainly block columnar aggregates. In the process of transformation from hemihydrate gypsum to dihydrate gypsum, the block columnar hemihydrate gypsum crystals gradually depolymerize and dissolve, and gradually crystallize to form dihydrate gypsum crystal nuclei. The crystal morphology of the growth is generally irregular granular and plate-like, and some granular crystals begin to show a flaky layered dissociation structure, which is the complex phase gypsum.

[0068] It can be seen that the complex phase gypsum is a metastable intermediate between the rapid transformation of hemihydrate gypsum to dihydrate gypsum, which is different from the regular crystal morphology of traditional hemihydrate gypsum, dihydrate gypsum, and the composite gypsum mixed in proportion with hemihydrate and dihydrate.

[0069] (2) Strength development principle of multiphase gypsum after secondary activation after crushing and water replenishment (second stage reaction, corresponding to step S3):

[0070] (0.33~0.67)(CaSO 4 0.5H 2O)·(0.33~0.67)(CaSO 4 ·2H 2 O)+(0.5~1.0)H 2 O→CaSO 4 ·2H 2 O.

[0071] After the complex phase gypsum is transported to the filling site, it is spread loosely for 50cm, and then crushed and watered. After crushing, the reaction area between particles increases. The secondary watering provides the driving force for the chemical reaction of the complex phase gypsum. After compaction and molding, when it is completely converted into 2H 2 O·CaSO 4 After that, a filling body with a certain strength (i.e., a multiphase gypsum foundation material) can be obtained.

[0072] Figure 4 This is a SEM image of a high-strength filling body formed by multiphase gypsum (with a crystal water content of 14.21%) after crushing, water replenishment, mixing, compaction and hydration.

[0073] Figure 5 This is a SEM image of a high-strength filling body formed by crushing, hydrating, mixing, compacting and hydrating hemihydrate gypsum (mass content of crystal water is 8.02%).

[0074] in, Figure 4 Figure a is a SEM image of a high-strength compact with a hydrated water content (mass content) of 17.72%; Figure 4 Figure b is a SEM image of a high-strength structure with a crystalline water content (mass content) hydrated to 19.02%;

[0075] in, Figure 5 Figure a is a SEM image of a high-strength compact with a hydrated water content (mass content) of 16.87%; Figure 5 Figure d in the figure is a SEM picture of a high-strength compact whose crystalline water content (mass content) is hydrated to 18.38%.

[0076] From the above SEM crystal morphology analysis, it can be seen that the strength of the hemihydrate gypsum and complex phase gypsum base materials mainly comes from the compaction and hydration of the crystals during the growth process, which interweave and overlap to form a structure with a certain strength.

[0077] However, the difference between hemihydrate gypsum and complex phase gypsum foundation materials is that the dissociation of dihydrate gypsum crystals formed after compaction and hydration is different. The dihydrate gypsum crystals formed by compaction and complete hydration of complex phase gypsum have the highest stratification dissociation ( Figure 4 b); After the hemihydrate gypsum is compacted and hydrated, the dihydrate gypsum crystals have the lowest dissociation, and the crystal structure is relatively complete compared to the complex phase gypsum ( Figure 5(b) Therefore, as the degree of delamination of the dihydrate gypsum structure increases, the strength decreases.

[0078] The present invention provides a preparation method of a highly stable multiphase gypsum foundation material and a supporting construction process flow. A highly stable multiphase gypsum foundation material between a semi-aqueous phase and a di-aqueous phase is prepared without adding a retarder or performing a drying treatment. The crystallization water conversion rate of the semi-hydrated gypsum is slowed down under the conditions of low free water content, high voids and high heat release, and the agglomeration strength is low, while a certain gelling activity can be maintained, thereby greatly reducing the cost of gypsum resource utilization and increasing the transportation radius.

[0079] The present invention adopts the road-mixing method for construction, saving the centralized factory mixing cost. After the complex phase gypsum is crushed, hydrated, mixed, and rolled into shape, it has high strength, good integrity, and low permeability coefficient, and can be widely used in industrial site foundation filling, ecological restoration, roadbed filling and other fields.

[0080] The present invention has no particular limitation on the sources of the raw materials used above, and they can be generally commercially available.

[0081] In order to further illustrate the present invention, a complex phase gypsum base material, a preparation method and application thereof provided by the present invention are described in detail below in combination with embodiments, but it should not be understood as limiting the scope of protection of the present invention.

[0082] The fresh semi-hydrated gypsum in the embodiments of the present invention and the comparative examples is an industrial byproduct of the semi-hydrated wet phosphoric acid production line of Guangxi Pengyue Ecological Technology Co., Ltd., with a free water content (mass content) of 17.55%, a crystal water content (mass content) of 6.34%, and a temperature of 56° C. The chemical compositions of the raw materials fresh semi-hydrated gypsum, as well as the modifier biomass ash powder, calcium carbonate powder, mining powder (powder and dust generated in the mining process of limestone mines, collected and sieved, referred to as mineral powder), water treatment slag, and calcium oxide dry powder are shown in Tables 1 to 6, all from the same batch.

[0083] Table 1 Chemical composition index of fresh hemihydrate gypsum (mass content, %), pH dimensionless

[0084]

[0085] Table 2 Chemical composition indexes of biomass ash powder (mass content, %), pH dimensionless

[0086]

[0087] Table 3 Chemical composition index of water treatment slag (mass content, %), pH dimensionless

[0088]

[0089] Table 4 Chemical composition indexes (mass content, %) of mining fine powder (mineral powder), pH dimensionless

[0090] Material Name Total CaO Available CaO pH Particle size ≤75um Mining powder (mineral powder) 49.21 5.11 7.56 100%

[0091] Table 5 Chemical composition index of calcium carbonate powder (mass content, %), pH dimensionless

[0092] Material Name Total CaO Available CaO pH Particle size ≤75um Calcium carbonate powder 51.03 10.11 10.00 100%

[0093] Table 6 Chemical composition index of calcium oxide powder (mass content, %), pH dimensionless

[0094] Material Name Total CaO Available CaO Calcium oxide powder 90.77 75.00

[0095] Example 1

[0096] 1) Mix the above-mentioned hemihydrate gypsum with CaCO 3 Micropowder, CaO dry powder and biomass ash micropowder are put into a double-shaft mixer for stirring and mixing according to a dry basis mass ratio of 93:3:1:3 to prepare modified semi-hydrated gypsum.

[0097] 2) The modified hemihydrate gypsum is transported to a stockpile for aging (stockpile conversion) for 2 days. The free water content (mass content) of the aged stockpile is 12.55%, the crystal water content (mass content) is 12.17%, the internal temperature of the stockpile is 55°C, and the particle strength of the stockpile is 0.21MPa. The low-strength blocks or particles with a particle size of ≤0.5MPa are broken up by an excavator or a forklift. The mass of the blocks or particles with a particle size of ≥4.75mm accounts for 90%, and the maximum particle size is 23cm. The internal temperature of the stockpile is released to 27°C to obtain a highly stable multiphase gypsum.

[0098] 3) The highly stable multiphase gypsum is transported to the filling site, laid loosely according to a thickness of 50 cm, and crushed by a deepened bullet-shaped mixing tooth road mixer (mixing depth ≥ 50 cm) (the multiphase gypsum has a particle size of ≤ 2 mm after crushing, accounting for 97%), and mixed with water (neutral water, the amount of water added is 6%). The free water content (mass content) of the obtained mixture is 18.55%, and the crystal water content (mass content) is 13.57%. Subsequently, a 25t heavy roller is used for compaction and molding, and the measured compaction degree is 92.11%. After 7 days of natural curing, the multiphase gypsum foundation material is obtained, and the crystal water content of the multiphase gypsum foundation material is hydrated to 20.00%. Core sampling work is carried out, and the representative value of R7d strength is 7.06MPa according to the T0805-94 standard method; the permeability coefficient is 1.70×10 -6 cm / s, reaching a permeability coefficient k of 10 -6 ≤K<10 -5The requirements have been met, greatly reducing the risk of surface water infiltration; the 28-day leaching toxicity meets the first-class solid waste standards, see Table 7 for details.

[0099] Example 2

[0100] 1) Mix the above-mentioned hemihydrate gypsum with CaCO 3 Micropowder, CaO dry powder and biomass ash micropowder are put into a double-shaft mixer for stirring and mixing according to a dry basis mass ratio of 93:3:1:3 to prepare modified semi-hydrated gypsum.

[0101] 2) The modified hemihydrate gypsum is transported to a stockpile for aging (stockpile conversion) for 2 days. The free water content (mass content) of the aged stockpile is 12.55%, and the crystal water content (mass content) is 12.17%; the internal temperature of the stockpile is 57°C; and the particle strength of the stockpile is 0.21MPa. The low-strength blocks or particles with a particle size of ≤0.5MPa are broken up by an excavator or a forklift. The mass of the blocks or particles with a particle size of ≥4.75mm accounts for 90%, and the maximum particle size is 23cm. The internal temperature of the stockpile is reduced to 25°C, and a highly stable multiphase gypsum is obtained.

[0102] 3) The multiphase gypsum obtained in step 2) was further stored for 8 days, at which time the free water content (mass content) was 11.45% and the crystallization water content (mass content) was 13.17%. An excavator and a forklift were used to break it up for the second time, and no obvious secondary agglomeration phenomenon was found, thereby obtaining a highly stable multiphase gypsum.

[0103] The storage time of multiphase gypsum is extended to 8 days. When the crystal water content is ≥12%, the pile should be turned and broken up in time to help release the internal temperature of the gypsum along the gaps. Under the common storage conditions of low moisture content, high porosity and high heat release, the stability is enhanced, and long-term storage and activity maintenance can be achieved, and the crystal water has only slightly transformed.

[0104] 4) The complex phase gypsum obtained in step 3) is transported to the filling site, laid loosely according to a thickness of 50 cm, and crushed by a deepened bullet-shaped mixing tooth road mixer (mixing depth ≥ 50 cm) (the particle size of the complex phase gypsum after crushing is ≤ 2 mm, accounting for 97%), and mixed with water (neutral water, the amount of water added is 6%). The free water content (mass content) of the obtained mixture is 18.33%, and the crystal water content (mass content) is 14.23%. Subsequently, a 25t heavy roller is used for compaction and molding, and the measured compaction degree is 92.34%. After 7 days of natural curing, the complex phase gypsum foundation material is obtained, and the crystal water content of the complex phase gypsum foundation material is hydrated to 19.98%. The core sampling work is carried out, and the representative value of the R7d strength is 6.50MPa according to the T0805-94 standard method; the permeability coefficient is 1.56×10 -6cm / s; 28d leaching toxicity meets the Class I solid waste standard, see Table 7 for details.

[0105] Example 3

[0106] 1) Mix the above-mentioned hemihydrate gypsum with CaCO 3 The micro powder is put into a double-shaft mixer for stirring and mixing according to a dry basis mass ratio of 95:5 to obtain modified hemihydrate gypsum.

[0107] The difference from Example 1 is that the modifier is changed to CaCO 3 The amount of the modified powder and modifier was adjusted; compared with Example 1, the conversion rate of the complex phase gypsum can be more effectively suppressed. It has a good slag removal effect on soluble P and F in an acidic or neutral environment, but the effect is worse than that of modifiers such as CaO dry powder and carbide slag, and the reaction age is longer. While ensuring the same gelling activity and most of the acidic ions such as P and F can be solidified, the aging time of the modified hemihydrate gypsum entering the yard needs to be extended from 2d to 15d. This technology is conducive to coping with the long-term storage in warehouses or yards in climatic environments that are not conducive to road transportation, such as continuous rainy days, and can maintain the gelling activity of gypsum to the greatest extent.

[0108] 2) The modified hemihydrate gypsum is transported to the stockpile for aging (stockpile conversion) for 15 days. The free water content (mass content) of the aged stockpile is 12.75%, the crystal water content (mass content) is 12.57%, the internal temperature of the stockpile is 59°C, and the particle strength of the stockpile is 0.23MPa. The low-strength blocks or particles with a particle size of ≤0.5MPa are broken up by excavators and forklifts. The mass proportion of the blocks or particles with a particle size of ≥4.75mm is 93%, and the maximum particle size is 24cm. The internal temperature of the stockpile is released to 23°C, and a highly stable multiphase gypsum is obtained.

[0109] 3) The highly stable multiphase gypsum is transported to the filling site, laid loosely according to a thickness of 50 cm, and crushed by a deepened bullet-shaped mixing tooth road mixer (mixing depth ≥ 50 cm) (the multiphase gypsum has a particle size of ≤ 2 mm after crushing, accounting for 97%), and mixed with water (using a water treatment slag slurry with a mass concentration of 15% (the solvent is water), and the dry basis mass ratio of water treatment slag to multiphase gypsum is 1:99). The free water content (mass content) of the obtained mixture is 18.23%, and the crystal water content (mass content) is 13.67%. Subsequently, a 25t heavy roller is used for rolling and forming, and the measured compaction degree is 92.33%. After 7 days of natural curing, a multiphase gypsum foundation material is obtained, and the crystal water content of the multiphase gypsum foundation material is hydrated to 20.12%. Core sampling was carried out. According to the T0805-94 standard method, the representative value of R7d strength was 7.23MPa. According to the T0130-2007 variable head method, the permeability coefficient was 1.56×10 -6cm / s; 28d leaching toxicity meets the Class I solid waste standard, see Table 7 for details.

[0110] Example 4

[0111] 1) The above-mentioned semi-hydrated gypsum and mineral powder are put into a double-shaft mixer at a dry basis mass ratio of 92:8 for stirring and mixing to obtain modified semi-hydrated gypsum.

[0112] The modifier was changed to mineral powder, and the dosage of the modifier was adjusted. Compared with Example 1, the conversion rate of the multiphase gypsum can be more effectively inhibited. However, the modification effect of mineral powder is worse than that of CaO dry powder, carbide slag, and CaCO 3 Modifiers such as micro powder have a certain solidification and slag removal effect on soluble P and F in an acidic or neutral environment, but the reaction age is relatively long. While ensuring the same gelling activity and the ability of most acidic ions such as P and F to solidify, the aging time of mineral powder modified hemihydrate gypsum entering the storage yard needs to be extended from 2 days to 15 days.

[0113] 2) The modified hemihydrate gypsum is transported to the stockpile for aging (stockpile conversion) for 15 days. The free water content (mass content) of the aged stockpile is 12.09%, and the crystal water content (mass content) is 12.47%; the internal temperature of the stockpile is 57°C; and the particle strength of the stockpile is 0.27MPa. The low-strength blocks or particles with a particle size of ≤0.5MPa are broken up by excavators and forklifts. The mass proportion of the blocks or particles with a particle size of ≥4.75mm is 91%, and the maximum particle size is 24cm. The internal temperature of the stockpile is released to 24°C to obtain highly stable multiphase gypsum.

[0114] 3) The highly stable multiphase gypsum is transported to the filling site, laid loosely according to a thickness of 50 cm, and crushed by a deepened bullet-shaped mixing tooth road mixer (mixing depth ≥ 50 cm) (the multiphase gypsum has a particle size of ≤ 2 mm after crushing, accounting for 97%), and mixed with water (using a water treatment slag slurry with a mass concentration of 25% (the solvent is water), and the dry basis mass ratio of water treatment slag to multiphase gypsum is 2:98). The free water content (mass content) of the obtained mixture is 18.00%, and the crystal water content (mass content) is 13.21%. Subsequently, a 25t heavy roller is used for compaction and molding, and the measured compaction degree is 92.01%. After 7 days of natural curing, a multiphase gypsum foundation material is obtained, and the crystal water content of the multiphase gypsum foundation material is hydrated to 20.16%. Core sampling was carried out. According to the T0805-94 standard method, the representative value of R7d strength was 7.79MPa. According to the T0130-2007 standard variable head method, the permeability coefficient was 1.56×10 -6 cm / s; 28d leaching toxicity meets the Class I solid waste standard, see Table 7 for details.

[0115] Comparative Example 1

[0116] The difference from Example 1 is:

[0117] The free water content (mass content) of the raw material hemihydrate gypsum in step 1) is increased from 17.55% to 25%, and the crystal water content (mass content) remains unchanged and is maintained at 6.34%.

[0118] 2) The modified hemihydrate gypsum is transported to the stockpile for aging (stockpiling conversion) for 2 days. The free water content (mass content) of the aged stockpile is 16.55%, the crystal water content (mass content) is 16.17%, and the internal temperature of the stockpile is 55°C; compared with Example 1, under a high free moisture content environment, the crystal water conversion rate is greatly accelerated, and the activity is continuously lost; at this time, the strength of the stockpile particles is also improved, which is 0.45MPa. The low-strength blocks or particles with a particle size of ≤0.5MPa are broken up by excavators and forklifts. The mass of the blocks or particles with a particle size of ≥4.75mm accounts for 90%, and the maximum particle size is 23cm. The internal temperature of the stockpile is released to 25°C. The obtained gypsum is aged, and it is impossible to prepare complex phase gypsum.

[0119] 3) The aged gypsum is transported to the filling site, laid loosely according to a thickness of 50 cm, and crushed by a deepened bullet-shaped mixing tooth road mixer (mixing depth ≥ 50 cm) (the particle size of the composite gypsum after crushing is ≤ 2 mm, accounting for 97%), water is added (neutral water, the amount of water added is 6%), and mixed. The free water content (mass content) of the obtained mixture is 18.09%, and the crystal water content (mass content) is 17.55%. Subsequently, a 25t heavy roller is used for rolling and molding, and the measured compaction degree is 93.00%. After 7 days of natural curing, the composite gypsum foundation material is obtained, and the crystal water content of the composite gypsum foundation material is hydrated to 20.02%. The core sampling work is carried out, and the representative value of R7d strength is 1.01MPa, which cannot meet the strength design requirement of the filling body ≥ 1.5MPa; according to the T0130-2007 variable head method, the permeability coefficient is 5.22×10 -5 cm / s, only reaches the weak permeability rock and soil permeability coefficient k of 10 -5 ≤K<10 -4 The risk of surface water infiltration increases; the 28-day leaching toxicity meets the first-class solid waste standard, see Table 7 for details.

[0120] Comparative Example 2

[0121] The difference from Example 2 is:

[0122] The free water content (mass content) of the raw material hemihydrate gypsum in step 1) is increased from 17.55% to 25%, and the crystal water content (mass content) remains unchanged and is maintained at 6.34%.

[0123] 2) The modified hemihydrate gypsum is transported to the stockpile for aging (stockpile conversion) for 2 days. The free water content (mass content) of the aged stockpile is 16.55%, the crystal water content (mass content) is 15.17%, and the internal temperature of the stockpile is 56°C; compared with Example 1, the crystal water conversion rate is greatly accelerated, and the activity is continuously lost; at this time, the strength of the stockpile particles is also improved, which is 0.45MPa. The low-strength blocks or particles with a particle size of ≤0.5MPa are broken up by excavators and forklifts. The mass of the blocks or particles with a particle size of ≥4.75mm accounts for 90%, and the maximum particle size is 23cm. The internal temperature of the stockpile is released to 22°C to obtain a complex phase gypsum.

[0124] 3) The obtained complex phase gypsum was further stored for 8 days. At this time, the free water content (mass content) was 14.45%, and the crystallization water content (mass content) was 17.17%. The crystallization water was further rapidly converted. The pile was broken up for the second time using an excavator and a forklift. It was found that the secondary agglomeration phenomenon of the pile was serious. The obtained gypsum was aged dihydrate gypsum, and the complex phase gypsum of the present invention could not be obtained.

[0125] 4) The aged dihydrate gypsum is transported to the filling site, laid loosely according to a thickness of 50 cm, and crushed by a deepened bullet-shaped mixing tooth road mixer (mixing depth ≥ 50 cm) (the particle size of the composite gypsum after crushing is ≤ 2 mm, accounting for 97%), and mixed with water (neutral water, the amount of water added is 1%). The free water content (mass content) of the obtained mixture is 18.12%, and the crystal water content (mass content) is 18.55%. Subsequently, a 25t heavy roller is used for rolling and molding, and the measured compaction degree is 93.23%. After 7 days of natural curing, a composite gypsum foundation material is obtained, and the crystal water content of the composite gypsum foundation material is hydrated to 19.69%. Core sampling work is carried out, and the representative value of R7d strength is 0.42MPa, which cannot meet the strength design requirement of the filling body ≥ 1.5MPa; according to the T0130-2007 variable head method, the permeability coefficient is 8.20×10 -5 cm / s, only reaches the weak permeability rock and soil permeability coefficient k of 10 -5 ≤K<10 -4 The risk of surface water infiltration increases; the 28-day leaching toxicity meets the first-class solid waste standard, see Table 7 for details.

[0126] Comparative Example 3

[0127] The difference from Example 1 is:

[0128] The alkaline modifier CaCO in step 1) 3 The proportion of powder, CaO dry powder and biomass ash powder increased, and the content of hemihydrate gypsum and CaCO 3The micro powder, CaO dry powder and biomass ash micro powder are mixed in a double-shaft mixer according to a dry basis mass ratio of 86:6:2:6 to obtain modified semi-hydrated gypsum.

[0129] 2) The modified hemihydrate gypsum is transported to the stockpile for aging (stockpile conversion) for 2 days. The free water content (mass content) of the aged stockpile is 8.55%, and the crystal water content (mass content) is 16.17%; the internal temperature of the stockpile rises to 70°C; the particle strength of the stockpile is 0.92MPa. The low-strength blocks or particles with a particle size of ≤0.5MPa are broken up by excavators and forklifts. The mass of the blocks or particles with a particle size of ≥4.75mm accounts for 90%, and the maximum particle size is 23cm. The internal temperature of the stockpile is released to 25°C. The material produced is aged dihydrate gypsum, and complex phase gypsum cannot be produced.

[0130] Compared with Example 1, with the increase in the amount of alkaline modifier, at the same storage conversion time, the crystal water content of the aged pile becomes higher, the internal temperature of the pile body also rises, the conversion rate is accelerated, and the activity loss is also accelerated. The main reason is that at an excessively high alkaline modifier dosage, sufficient reaction driving force is provided for the conversion of crystal water in the hemihydrate gypsum. At the same time, the reaction process is too intense, generating a large amount of hydration heat, which makes the stability of the multiphase gypsum worse. Even after being broken up and crushed by an excavator, the conversion rate is still fast under the conditions of low moisture content and high porosity, and the risk of secondary storage agglomeration is further increased. Therefore, it is necessary to minimize the amount of alkaline modifier, or use CaCO 3 Used in combination with low hydration thermal modifiers such as micro powder and mineral powder.

[0131] 3) The aged dihydrate gypsum was transported to the construction site, laid loosely according to a thickness of 50 cm, and crushed using a deepened bullet-shaped mixing tooth road mixer (mixing depth ≥ 50 cm) (the particle size of the composite gypsum after crushing ≤ 2 mm accounted for 97%), and water was added and mixed (neutral water, the amount of water added was 10%). The free water content (mass content) of the obtained mixture was 18.56%, and the crystal water content (mass content) was 17.65%. Subsequently, a 25t heavy roller was used for rolling and molding, and the measured compaction degree was 93.23%. After 7 days of natural curing, a composite gypsum foundation material was obtained, and the crystal water content of the composite gypsum foundation material was hydrated to 20.11%. Core sampling work was carried out, and the representative value of R7d strength was 0.73MPa, which could not meet the strength design requirement of the fill body ≥ 1.5MPa; according to the T0130-2007 variable head method, the permeability coefficient was 8.90×10 -5 cm / s, only reaches the weak permeability rock and soil permeability coefficient k of 10 -5 ≤K<10 -4 The risk of surface water infiltration increases; the 28-day leaching toxicity meets the first-class solid waste standard, see Table 7 for details.

[0132] The 28-day leaching toxicity of the complex phase gypsum base building materials prepared in Examples 1 to 4 and Comparative Examples 1 to 3 was tested, and the results are shown in Table 7.

[0133] Table 7 28d leaching toxicity test results of multiphase gypsum foundation materials

[0134]

[0135] Notes: (1) "Not" in Table 7 means not detected, which is below the detection limit. (2) The concentrations of heavy metal ions such as total chromium, total ion, total copper, total nickel, total manganese, total zinc, total mercury, and total arsenic in the leaching toxicity of Examples 1 to 4 and Comparative Examples 1 to 3 in Table 7 were not detected.

[0136] It can be seen from Table 7 that the 28-day natural curing samples of the multiphase gypsum foundation materials prepared by Examples 1 to 4 and Comparative Examples 1 to 3, according to the pretreatment method "HJ557-2010-Solid Waste Leaching Toxicity Leaching Method Horizontal Oscillation Method" prepared in the leaching toxic night TP, fluoride, NH 3 -N, pH, and heavy metal ions such as total chromium, total ions, total copper, total nickel, total manganese, total zinc, total mercury, and total arsenic all meet the Class I solid waste standards in the "General Industrial Solid Waste Storage and Landfill Pollution Control Standards" (GB 18599-2020) and the "Technical Specifications for Pollution Control of Phosphogypsum Ecological Restoration Projects" (T / GZHX 002-2024) The requirements for harmless treatment of phosphogypsum.

[0137] The crystal water conversion rates of the complex phase gypsum prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were tested, and the results are shown in Table 8.

[0138] Table 8 Test results of crystal water conversion rate of multiphase gypsum foundation material

[0139]

[0140] Table 9 Construction process indicators of multiphase gypsum foundation materials and test results of fill performance

[0141]

[0142] It can be seen from Example 1 and Comparative Example 1 in Tables 8 and 9 that when the free water in the initial hemihydrate gypsum is increased from 17.55% to 25%, the crystal water of the prepared multiphase gypsum increases from 12.17% to 16.55% when stored for the same time of 2 days, and the conversion rate increases significantly. The stockpile strength of the multiphase gypsum in the aged yard before crushing also increases from 0.21MPa to 0.45MPa, and the difficulty of excavator breaking up increases. After being broken up by the excavator, the representative value of the R7d compressive strength after being transported to the construction site for crushing, hydration, mixing, and rolling is also reduced from 7.06MPa to 1.01MPa, and the permeability coefficient is also reduced from 1.7×10 -6 cm / s increased to 5.22×10 -5 cm / s.

[0143] It can be seen from Example 1 and Comparative Example 2 in Tables 8 and 9 that when the free water in the initial hemihydrate gypsum increases from 17.55% to 25%, the complex phase gypsum continues to be stored after being broken up and crushed, and continues to rapidly transform under the action of high free water content (16.55%). When it is stored for 8 days, not only is the secondary agglomeration serious, but the final product is aged gypsum, not complex phase gypsum. After being broken up and crushed by an excavator, it is transported to the construction site for crushing, water replenishment, mixing, and rolling. The representative value of the R7d compressive strength is also reduced from 7.06MPa to 0.42MPa, and the permeability coefficient is also reduced from 1.7×10 -6 cm / s increased to 8.22×10 -5 cm / s.

[0144] It can be seen from Example 1 and Comparative Example 3 in Tables 8 and 9 that as the amount of alkaline modifier increases to 2 times, under the same storage conversion time (2d), the crystal water content of the aged pile increases from 12.17% to 16.17%, the internal temperature rises from 55°C to 70°C, the conversion rate is accelerated, and the activity loss is accelerated; the pile strength increases from 0.21MPa to 0.92MPa, resulting in the prepared multiphase gypsum excavator being difficult to crush and inefficient; the representative value of the R7d compressive strength after being transported to the construction site, crushed, hydrated, mixed, and rolled is also reduced from 7.06MPa to 0.73MPa, and the permeability coefficient is also reduced from 1.76×10 -6 cm / s increased to 9.22×10 -5 cm / s. The main reason is that when the alkaline modifier dosage is too high, it provides sufficient reaction driving force for the transformation of crystal water in hemihydrate gypsum, making the stability of the complex phase gypsum worse. Even after being broken up and crushed by the excavator, the risk of secondary storage agglomeration is further increased under the conditions of water content and high porosity. Therefore, the dosage of alkaline modifier should be minimized. The optimal dosage is the amount of modifier required to make the gypsum impurity removal just meet the first-class solid waste standard; or use CaCO 3The use of low hydration thermal modifiers such as micropowder and mineral powder can reduce the intensity of the hydration reaction.

[0145] The composite gypsum foundation material prepared by the present invention is used for ecological restoration of abandoned mine pits in Guangxi. The filling body has high strength, good density, low permeability and anti-scouring. The strength can meet the requirements of the mine structure design strength ≥1.5MPa; the permeability reaches the micro-permeable rock and soil permeability coefficient k of 10 -6 ≤K<10 -5 The requirements of the multiphase gypsum base material greatly reduce the risk of surface water infiltration; the multiphase gypsum base material meets the Class I solid waste standards in the "General Industrial Solid Waste Storage and Landfill Pollution Control Standards" (GB 18599-2020), and the harmless treatment requirements of phosphogypsum in the "Technical Specifications for Pollution Control of Phosphogypsum Ecological Restoration Projects" (T / GZHX 002-2024).

[0146] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for preparing a multiphase gypsum foundation material, comprising the following steps: S1) stirring and mixing the semi-hydrated gypsum and the modifier to obtain modified semi-hydrated gypsum; The initial free water content of the hemihydrate gypsum is ≤18.0%, and the crystal water content is ≤9.0%; S2) the modified hemihydrate gypsum is piled up and converted and then dispersed to obtain xCaSO4·0.5H2O·(1-x)CaSO4·2H2O type multiphase gypsum; wherein x=0.33-0.67; S3) crushing the complex phase gypsum, adding water, mixing, compacting and forming to obtain a complex phase gypsum foundation material.

2. The preparation method according to claim 1, characterized in that: In step S1), the chemical components of the hemihydrate gypsum include: SO3 40 wt% ~ 55wt%, CaO 30wt% ~ 35wt%, SiO2 2 wt% ~ 5wt%, Al2O3 0.1wt% ~ 2wt%, Fe2O3 0 wt% ~ 0.5wt%, MgO 0wt% ~ 0.2wt%, total P2O5 0.5 wt% ~ 1.5wt%, water-soluble P2O5 0.01 wt% ~ 0.7wt%, total F 0.2wt% ~ 1.5wt%, water-soluble F 0.02wt% ~ 0.5wt%, K2O 0.01wt% ~ 0.2wt%, Na2O 0.1wt% ~ 0.5wt%.

3. The preparation method according to claim 1, characterized in that: In step S1), the modifier includes at least one of calcium oxide, magnesium carbonate, cement, carbide slag, water treatment slag, mineral powder, biomass ash powder and CaCO3 powder.

4. The preparation method according to claim 1, characterized in that: In step S1), the mass ratio of the modifier to the semi-hydrated gypsum dry matrix is ​​2-10:90-98.

5. The preparation method according to claim 1, characterized in that: In step S2), the storage conversion time is 10h to 15d; the particle strength of the pile is ≤0.5MPa; In the stockpile after the stockpile conversion, the free water content is ≤14%, and the crystal water content is 12% to 16%.

6. The preparation method according to claim 1, characterized in that: In step S2), the low-strength blocks or particles with a mass of ≤0.5MPa are broken up; among the low-strength blocks or particles, the mass proportion of blocks or particles with a particle size of ≥4.75mm is more than 80%, and the maximum particle size does not exceed 25cm; the breaking up is carried out using an excavator and / or a forklift.

7. The preparation method according to claim 1, characterized in that: In step S3), the crushing device adopts a road mixer, and uses a deepened bullet-shaped stirring tooth, the stirring depth is ≥50cm, and the particle size of the composite gypsum after crushing is ≤2mm accounts for more than 90%.

8. The preparation method according to claim 1, characterized in that: In step S3), the free water content of the mixed material after water replenishment and mixing is 18% to 20%, and the crystal water content is 12% to 16%; The compaction degree of the compacted body after compaction molding is ≥90%.

9. The multiphase gypsum foundation material obtained by the preparation method according to any one of claims 1 to 8.

10. Use of the multiphase gypsum foundation material according to claim 9 in the fields of industrial site foundation filling, ecological restoration and roadbed filling.

Citation Information

Cited By

  • Preparation method of complex-phase ardealite-based semi-rigid roadbed material

    CN121449369A